Wide-temperature-range high-pressure-ratio titanium-based hydrogen storage alloy, and preparation method and application thereof
Patent Information
- Application Number
- CN202611192055.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-13
AI Technical Summary
然而,传统机械压缩机存在以下固有缺陷:(1)结构复杂且易损件多:机械运动部件频繁磨损,维护成本高,故障率高;(2)存在介质污染风险:润滑油或密封介质可能渗入氢气,降低氢气纯度,进而毒化下游质子交换膜燃料电池(PEMFC);(3)能耗高且噪声巨大:需消耗大量电能,且运行噪音大,无法直接利用低品位工业废热
(1)单参数精细调控与极高压缩比:仅通过调整变量x(0.22≤x≤0.3),即可在10℃下实现≤0.3MPa吸氢,在250℃下实现≥15MPa(甚至达18 MPa)放氢,热驱动压差比超过50倍。
Smart Images

Figure CN122898767A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of metal hydrogen storage and solid hydrogen compression technology, specifically to an AB2 type titanium-based hydrogen storage and booster alloy with low hydrogen absorption pressure, ultra-high hydrogen release pressure, and wide temperature range and high pressure ratio suitable for thermally driven solid hydrogen compressors, as well as its preparation method and application. Background Technology
[0002] In the hydrogen energy industry chain, the storage and transportation of hydrogen and high-pressure refueling (such as 35 MPa / 70 MPa hydrogen refueling stations and high-pressure hydrogen storage cylinder filling) are key links connecting the hydrogen production end and the hydrogen consumption end. At present, the industry mainly relies on mechanical compressors (such as diaphragm compressors and piston compressors) to pressurize hydrogen. However, traditional mechanical compressors have the following inherent defects: (1) complex structure and many vulnerable parts: frequent wear of mechanical moving parts, high maintenance costs and high failure rate; (2) risk of medium contamination: lubricating oil or sealing medium may seep into hydrogen, reduce the purity of hydrogen, and thus poison the downstream proton exchange membrane fuel cell (PEMFC); (3) high energy consumption and huge noise: it requires a lot of electrical energy and has a lot of operating noise, and cannot directly utilize low-grade industrial waste heat.
[0003] In contrast, the solid metal hydrogen compressor (MHHC), based on the reversible thermodynamic reaction of metal hydrides, utilizes the hydrogen absorption / desorption pressure difference of the alloy under low heat energy to achieve pressurization. It has significant advantages such as no moving mechanical parts, quiet operation, no oil pollution, extremely high safety, and direct utilization of low-grade industrial waste heat or solar energy at 100℃-200℃. It is an important development direction for the next generation of green hydrogen pressurization storage and transportation technology.
[0004] In practical engineering applications, thermally driven solid-state hydrogen compressors typically require: at relatively low temperatures (such as around 10°C cooling water or ambient temperature), to spontaneously and efficiently absorb hydrogen using extremely low-pressure source gas (such as <0.3MPa hydrogen produced by water electrolysis or industrial by-product hydrogen); subsequently, by heating with a low-grade heat source (such as around 250°C), the alloy releases hydrogen gas at ultra-high pressure (such as 15MPa or even above 18MPa), thereby achieving thermally driven ultra-high pressure differential compression that spans two orders of magnitude (up to 50 times or more).
[0005] Among existing solid-state hydrogen storage alloy systems, AB2-type (Ti-Mn or Ti-Zr-Mn) Laves phase alloys are considered the best candidate materials for thermally driven high-pressure hydrogen compressors due to their fast reaction kinetics, high hydrogen storage capacity, and strong resistance to poisoning. However, facing the extreme dual requirements of "low hydrogen absorption pressure (<0.3MPa@10℃)" and "ultra-high hydrogen release pressure (>15MPa@250℃)," existing AB2-type alloys still suffer from the following fatal physical and thermodynamic bottlenecks: (1) The deep internal friction and contradiction between the thermodynamic expansion of the unit cell and the high-temperature hydrogen release pressure According to the thermodynamic van 't Hoff equation for metal-hydrogen reactions:
[0006] The hydrogen absorption / desorption plateau pressure depends directly on the enthalpy change of the reaction. ) and cell volume. In traditional AB2 alloy design: To reduce the hydrogen absorption pressure at 10°C to below 0.3 MPa, it is usually necessary to introduce elements with large atomic radii (such as Zr, La, etc.) to expand the unit cell volume. This will lead to a significant increase in the absolute value of the reaction enthalpy change ΔH, and the formation of overly stable hydrides. The excessive stability of the hydrides makes the energy barrier to be overcome for thermal dehydrogenation at 250°C extremely high, and the high-temperature hydrogen release pressure decays rapidly, often only reaching 5-8 MPa, far below the ultra-high pressure output threshold of 15 MPa. Conversely, if strong pressure-boosting elements (such as Fe, Ni, etc.) are added to increase the hydrogen release pressure at 250°C, it will cause a sharp increase in the hydrogen absorption plateau pressure at 10°C (usually > 0.8 MPa), making it impossible for the low-pressure source gas of 0.3 MPa to spontaneously fill the alloy, and the pressurization process cannot be started at all.
[0007] (2) The hydrogen absorption and desorption hysteresis phenomenon is severe, and the effective hydrogen desorption capacity in the high-pressure section is significantly reduced. Solid-state booster alloys exhibit lattice deformation strain energy during hydrogen absorption and desorption, manifested as a hydrogen absorption plateau pressure (P). ads The pressure is significantly higher than the hydrogen desorption plateau pressure (P). des Traditional multi-component AB2 alloys, when pursuing high pressure output, often suffer from incoordination in microscopic phase transformation, leading to a hysteresis coefficient In(P). ads / P des (It increases dramatically.)
[0008] Even if heating to 250℃ allows the theoretical hydrogen absorption pressure to reach 20 MPa, due to the significant hysteresis effect, the practically usable hydrogen release plateau pressure (P0) is limited. des The pressure dropped sharply to below 12 MPa. This results in a large amount of hydrogen being "locked" in the alloy lattice and unable to be released, causing a sharp drop in the effective hydrogen release capacity under high pressure (usually reduced to < 0.8wt%), which greatly reduces the single-cycle working efficiency of the compressor.
[0009] (3) Excessive slope factor leads to a sharp deterioration in compression ratio under high pressure. Existing high-pressure AB2 alloys generally suffer from microscopic compositional segregation and disordered precipitation of the second phase, resulting in an excessively steep slope of the PCT (pressure-composition-temperature) curve and a lack of smoothness in the plateau region. During ultra-high pressure (>15MPa) hydrogen release processes, the release pressure drops sharply with the increase in hydrogen release volume, making it impossible to maintain a stable high-pressure output. Consequently, solid-state compressors cannot provide a constant high-pressure hydrogen flow in actual operation.
[0010] (4) The multivariate coupling of component regulation is out of control, making it difficult to form an industrially controllable manufacturing process. Traditional AB2 alloy modification often adopts the approach of "disordered substitution of multiple elements" (simultaneously and independently changing multiple variables such as Ti / Zr, Mn / Cr / V / Fe). The effects of different elements on cell volume, electron density and enthalpy change are intertwined and difficult to decouple, resulting in the material being extremely sensitive to composition during actual melting. The thermodynamic properties during mass production have extremely poor repeatability and cannot meet the stable use requirements of industrial-grade high-pressure boosting systems.
[0011] In summary, developing a wide-temperature-range, high-pressure hydrogen storage and boosting alloy that can overcome the contradiction between low hydrogen absorption pressure and ultra-high hydrogen release pressure, has a small hysteresis effect, a flat plateau, and can be precisely thermodynamically controlled through a simplified composition is an urgent task to break through the engineering bottleneck of solid-state hydrogen compression technology. Summary of the Invention
[0012] The purpose of this invention is to provide a wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy, its preparation method, and its application. This alloy is a single-parameter linkage-controlled AB2-type booster alloy with a hydrogen absorption pressure ≤0.3MPa at 10℃ and a hydrogen release pressure ≥15MPa at 250℃, achieving thermally driven high pressure differential compression of over 50 times, while also exhibiting excellent plateau flatness and cycle stability.
[0013] To achieve the above objectives, the present invention provides the following technical solution: A wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy with the general chemical formula Ti 1-x Zr x Cr 0.7 Mn 0.7 Mo 0.2 V 0.5- x Fe x-0.1The variable modulus parameter x has a range of values of 0.22≤x≤0.30.
[0014] Among them, the analysis of the single-parameter x-coordinated regulation mechanism is as follows: (1) Strictly conforms to the chemical specifications of AB2 crystals: The total number of atoms on side A is: (1-x) + x = 1.0; The total number of atoms on side B is: 0.7 + 0.7 + 0.2 + (0.5-x) + (x-0.1) = 2.0; The overall B / A ratio is maintained at 2.0 to ensure the formation of a single, stable C14 or C15 Laves phase.
[0015] (2) Thermodynamic synergistic compensation on the A / B sides: Low-temperature hydrogen absorption protection (≤0.3MPa@10℃): When x is increased, the large radius Zr on side A increases (0.22-0.3), and the cell volume is significantly expanded, which effectively suppresses the problem of excessively high hydrogen absorption pressure caused by the increase of Fe on side B, and ensures smooth intake of low-pressure source gas.
[0016] High-temperature hydrogen release burst (≥15MPa@250℃): Increasing x causes a synchronous increase in Fe, the element that strongly boosts pressure on side B (x-0.1), in conjunction with fixing a high content of Cr. 0.7 Mn 0.7 Mo 0.2 This method adjusts the stability of alloy hydrides, reduces the thermodynamic resistance to hydrogen release, and increases the high-temperature hydrogen release platform pressure, enabling the high-temperature dehydrogenation pressure at 250℃ to easily exceed 15 MPa.
[0017] The preparation method of the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy of the present invention includes the following steps: (1) Batching and smelting: Weigh high-purity metal raw materials according to the general formula ratio and place them in a non-consumable vacuum titanium substrate electric arc furnace or a vacuum induction melting furnace; perform multiple turning and smelting under the protection of high-purity argon gas to ensure uniform composition; (2) Homogenization heat treatment: The smelted alloy ingot is placed in a vacuum heat treatment furnace and held at 980℃-1050℃ for 12-24 hours, and then quenched to room temperature to eliminate microsegregation. (3) Mechanical crushing and activation: The heat-treated alloy block is crushed to 40-100 mesh under inert gas protection and activated by passing 1-3 MPa of high-purity hydrogen at room temperature.
[0018] The purity of the high-purity metal raw material is ≥99.99%.
[0019] The purity of the high-purity argon gas is ≥99.999%.
[0020] The quenching process is carried out by water quenching or rapid air cooling.
[0021] The number of times the melting process is flipped is no less than four.
[0022] The wide-temperature-range, high-pressure ratio titanium-based hydrogen storage and booster alloy described in this invention can be used in the preparation of thermally driven solid hydrogen compressors.
[0023] Compared with the prior art, the beneficial effects of the present invention are: (1) Single-parameter fine control and extremely high compression ratio: By adjusting the variable x (0.22≤x≤0.3), hydrogen absorption of ≤0.3MPa can be achieved at 10℃ and hydrogen release of ≥15MPa (even up to 18 MPa) at 250℃, with a thermally driven pressure difference ratio of more than 50 times.
[0024] (2) The platform has a small slope and high effective capacity: utilizing Cr 0.7 Mn 0.7 Mo 0.2 The high base ratio effectively smooths the slope of the PCT platform, reduces the hydrogen absorption and desorption hysteresis, and has an effective hydrogen desorption capacity of ≥1.25wt%.
[0025] (3) Rapid activation and cycle stability: No high-temperature pretreatment is required for the first hydrogen absorption. It can be rapidly activated by passing hydrogen at room temperature. After 1000 cycles of ultra-high pressure hydrogen absorption and desorption, the capacity retention rate is ≥90%. Attached Figure Description
[0026] Figure 1 This is a flowchart of the alloy preparation and testing process.
[0027] Figure 2 The PCT curves for hydrogen absorption at 10°C are for Examples 1-3 and Comparative Examples 1-2.
[0028] Figure 3 The PCT curves for hydrogen release at 250°C are for Examples 1-3 and Comparative Examples 1-2. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] like Figure 1 As shown, the alloys used in the embodiments and comparative examples of this invention were prepared and their performance tested according to the following standardized procedures: (1) Batching and smelting: Weigh high-purity metal raw materials (Ti, Zr, Cr, Mn, Mo, V, Fe, all with a purity greater than 99.95%) according to the molar ratio in the designed chemical formula. Place the raw materials in a non-consumable vacuum titanium substrate electric arc furnace and evacuate to 5.00 × 10⁻⁶. -3 Next, high-purity argon gas (purity > 99.999%) is introduced to -0.05MPa for arc melting. The alloy is repeatedly turned and melted 4 times during the melting process to ensure high uniformity of microstructure.
[0031] (2) Homogenization heat treatment: The alloy ingot obtained from melting is wrapped with high-purity tantalum foil and sealed in a vacuum quartz tube (vacuum degree <10). -3 The quartz tube was placed in a muffle furnace and held at 1020℃ for 18 hours. After annealing, the quartz tube was quickly removed, crushed, and quenched in ice water to obtain a single-phase C14 type Laves phase structure.
[0032] (3) Mechanical crushing and activation test: The annealed alloy ingot was mechanically crushed to 40-100 mesh (particle size about 150-380µm) in an argon glove box and placed into the reaction chamber of a Sievert type high-pressure PCT (pressure-composition-temperature) thermodynamic tester. High-purity hydrogen gas (purity 99.999%) was introduced at room temperature at 3.0MPa, and the alloy could spontaneously complete the first activation within 3 minutes.
[0033] (4) PCT thermodynamics and cyclic testing: Hydrogen absorption test (10℃): The reaction chamber was kept at a constant temperature of 10℃. Hydrogen was gradually added starting from 0.01 MPa. After the hydrogen absorption pressure reached 7.0 MPa, hydrogen was gradually evacuated and released. The hydrogen absorption and release PCT curves were measured, and the hydrogen absorption plateau pressure P was read at a hydrogen storage capacity of H / M=0.5. abs ; Hydrogen release test (250℃): The reaction chamber is heated to 250℃ and kept at that temperature. Hydrogen is gradually added starting from 0.01MPa. After the hydrogen absorption pressure reaches 7.0MPa, hydrogen is gradually released by evacuation. The hydrogen release PCT curve is measured, and the hydrogen release plateau pressure P is read at the hydrogen storage capacity H / M=0.5. des ; Lag factor calculation: According to the formula Hysteresis = In(P) abs / P des Calculate the hysteresis factor at the same temperature; 1000-cycle ultra-high pressure test: Under the set program of hydrogen absorption at 10℃ (0.3 MPa hydrogen source) and hydrogen release by heating at 250℃ (high pressure holding 15 MPa), 1000 cycles of hydrogen absorption and release were automatically performed, and the capacity retention rate was calculated.
[0034] Example 1: (x=0.23, optimized for extremely low hydrogen absorption pressure) Alloy composition: Ti 0.77 Zr 0.23 Cr 0.7 Mn 0.7 Mo 0.2 V 0.27 Fe 0.13 Design purpose: For extreme scenarios with extremely low source gas pressure (such as the hydrogen production outlet of water electrolysis at 0.20-0.25 MPa), by setting a lower x value (0.23), the Fe content is reduced to 0.13, further reducing the low-temperature hydrogen absorption plateau pressure.
[0035] Test results: 10℃ hydrogen absorption plateau pressure P abs : 0.21 MPa (fully meets the requirement of ≤0.3MPa, and leaves sufficient safety margin). 250℃ hydrogen release plateau pressure P des 15.2 MPa (meets ≥15MPa output); Maximum hydrogen storage capacity: 1.65 wt%; Effective hydrogen release capacity (0.3-15 MPa range): 1.41 wt%; Capacity retention after 1000 cycles: 90.5%.
[0036] Example 2: (x=0.26, optimal overall balance type) Alloy composition: Ti 0.74 Zr 0.26 Cr 0.7 Mn 0.7 Mo 0.2 V 0.24 Fe 0.16 Design objective: As the golden middle point of this invention, while ensuring that the hydrogen absorption pressure is firmly locked at 0.25 MPa at 10°C, the hydrogen release pressure at 250°C is compressed to close to 17 MPa, thereby achieving a higher compression ratio.
[0037] Test results: 10℃ hydrogen absorption plateau pressure P abs 0.25 MPa; 250℃ hydrogen release plateau pressure P des 16.8 MPa (thermally driven compression ratio up to 67.2 times); Maximum hydrogen storage capacity: 1.62 wt%; Effective hydrogen release capacity: 1.41 wt%; Capacity retention after 1000 cycles: 90.5%.
[0038] Example 3: (x=0.29, ultra-high hydrogen release pressure optimized) Alloy composition: Ti0.71 Zr 0.29 Cr 0.7 Mn 0.7 Mo 0.2 V 0.21 Fe 0.19 Design purpose: For scenarios where the low-pressure source gas is 0.30 MPa, but the target filling pressure needs to be above 18 MPa (such as a 20 MPa solid hydrogen storage cylinder). When x=0.29, the Fe content reaches 0.19, providing extremely strong high-temperature dehydrogenation thermodynamics.
[0039] Test results: 10℃ hydrogen absorption plateau pressure P abs 0.29 MPa (close to the upper limit but not exceeding it); 250℃ hydrogen release plateau pressure P des : 18.4 MPa (heat-driven compression ratio up to 63.4 times); Maximum hydrogen storage capacity: 1.54 wt%; Effective hydrogen release capacity: 1.35 wt%; Capacity retention after 1000 cycles: 90.2%.
[0040] To highlight the beneficial effects of the present invention, the following comparative experiments are provided.
[0041] Comparative Example 1: (x=0.20, lower than the lower limit defined in this invention) Alloy composition: Ti 0.80 Zr 0.20 Cr 0.7 Mn 0.7 Mo 0.2 V 0.30 Fe 0.10 Defect analysis: When x=0.20, the Fe content drops to 0.10, and the Zr content is also low. Although the hydrogen absorption pressure at 10℃ is very low (0.16MPa), the hydrogen release plateau pressure at 250℃ is only 12.1 MPa, which cannot reach the hard target of 15 MPa, causing the high-pressure section of the solid-state compressor to fail.
[0042] Comparative Example 2: (x=0.32, higher than the upper limit specified in this invention) Alloy composition: Ti 0.68 Zr 0.32 Cr 0.7 Mn 0.7 Mo 0.2 V 0.18 Fe 0.22 Defect analysis: When x=0.32, the Fe content is too high (0.22). Although the hydrogen release pressure surges to 19.8 MPa at 250℃, the hydrogen absorption plateau pressure rises sharply to 0.38 MPa at 10℃. Under a source gas pressure of 0.30 MPa, the alloy cannot spontaneously absorb hydrogen, and the pressurization system cannot be started at all.
[0043] The PCT curves of hydrogen absorption at 10°C for Examples 1-3 and Comparative Examples 1-2 are as follows: Figure 2 As shown, the PCT curve for hydrogen desorption at 250℃ is as follows: Figure 3 As shown in the figure. The relevant data is shown in the table below.
[0044]
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy, characterized in that: The general chemical formula is Ti 1- x Zr x Cr 0.7 Mn 0.7 Mo 0.2 V 0.5-x Fe x-0.1 The variable modulus parameter x has a range of values of 0.22≤x≤0.
30.
2. The wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy according to claim 1, characterized in that: It is a C14 or C15 type Laves phase.
3. The wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy according to claim 1, characterized in that: The hydrogen absorption pressure is ≤0.3MPa at 10℃.
4. The wide-temperature-range, high-pressure titanium-based hydrogen storage booster alloy according to claim 1, characterized in that: The hydrogen release pressure is ≥15 MPa at 250℃.
5. The method for preparing the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Batching and smelting: Weigh high-purity metal raw materials according to the general formula ratio and place them in a non-consumable vacuum titanium substrate electric arc furnace or a vacuum induction melting furnace; perform multiple turning and smelting under the protection of high-purity argon gas to ensure uniform composition; (2) Homogenization heat treatment: The smelted alloy ingot is placed in a vacuum heat treatment furnace and held at 980℃-1050℃ for 12-24 hours, and then quenched to room temperature to eliminate microsegregation; (3) Mechanical crushing and activation: The heat-treated alloy block is crushed to 40-100 mesh under inert gas protection and activated by passing 1-3 MPa of high-purity hydrogen at room temperature.
6. The preparation method of the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy according to claim 5, characterized in that: The purity of the high-purity metal raw material is ≥99.99%.
7. The preparation method of the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy according to claim 5, characterized in that: The purity of the high-purity argon gas is ≥99.999%.
8. The preparation method of the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy according to claim 5, characterized in that: The quenching is performed by water quenching or rapid air cooling.
9. The preparation method of the wide-temperature-range high-pressure titanium-based hydrogen storage booster alloy according to claim 5, characterized in that: The number of times the smelting process is flipped is no less than four.
10. The application of the wide-temperature-range, high-pressure-ratio titanium-based hydrogen storage and booster alloy according to any one of claims 1-4 in a thermally driven solid hydrogen compressor.